Evaluation of several microcrystalline celluloses obtained from agricultural by-products (2011)
ABSTRACT: Microcrystalline cellulose (MCCI) has been widely used as an excipient for direct compression due to its good flowability, compressibility, and compactibility. In this study, MCCI was obtained from agricultural by-products, such as corn cob, sugar cane bagasse, rice husk, and cotton by pursuing acid hydrolysis, neutralization, clarification, and drying steps. Further, infrared spectroscopy (IR), X-ray diffraction (XRD), optical microscopy, degree of polymerization (DP), and powder and tableting properties were evaluated and compared to those of Avicel PH101, Avicel PH102, and Avicel PH200. Except for the commercial products, all materials showed a DP from 55 to 97. Particles of commercial products and corn cob had an irregular shape, whereas bagasse particles were elongated and thick. Rice and cotton particles exhibited a flake-like and fiber-like shape, respectively. MCCI as obtained from rice husk and cotton was the most densified material, while that produced from corn cob and bagasse was bulky, porous, and more compressible. All products had a moisture content of less than 10% and yields from 7.4% to 60.4%. MCCI as obtained from bagasse was the most porous and compressible material among all materials. This product also showed the best tableting properties along with Avicel products. Likewise, all MCCI products obtained from the above-mentioned sources showed a more rapid disintegration time than that of Avicel products. These materials can be used as a potential source of MCCI in the production of solid dosage forms.